Diversity of Moraxella spp. strains recovered from infectious bovine keratoconjunctivitis cases in Uruguay - Sosa, Vanessa; Zunino, Pablo (The Journal of Infection in Developing Countries, 2013)
Background: Infectious bovine keratoconjunctivitis (IBK) is the most common ocular disease that affects cattle throughout the world and it has a very significant economic impact. IBK is caused by members of the genus Moraxella and therapeutic and preventive measures have shown limited success. Vaccines, most of them chemically inactivated bacterins, generally induce a limited protection. Methodology: In this study, the genetic diversity of Uruguayan clinical Moraxella bovis and Moraxella bovoculi isolates was assessed by RAPD-PCR, ERIC-PCR and BOX-PCR fingerprinting. Also, antibiotic resistance of the Moraxella spp. isolates was assessed utilizing the disk diffusion method. Results: When interspecific molecular diversity was assessed, different bands patterns were observed even within a single outbreak of IBK, showing the coexistence of different genotypes of Moraxella spp. The high genetic diversity within M. bovis and M. bovoculi isolates did not permit to correlate isolates DNA fingerprints with geographical origins, dates or even with both different Moraxella species. Antibiotics resistance patterns showed significant differences between M. bovis and M. bovoculi. Conclusions: This is the first study of diversity that includes M. bovis and M. bovoculi associated to IBK cases. Genetic diversity did not allow to correlate DNA fingerprints of the isolates with geographical origins, isolation dates or even both different Moraxella species. Antibiotics resistance patterns showed differences between M. bovis and M. bovoculi. This remarkable variation within isolates could explain the partial protection induced by commercial vaccines. All these findings could be important for the design of prevention or treatment strategies against IBK.